2019
DOI: 10.3390/lubricants7040038
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical, Mechanical, and Tribological Analysis of DLC Coatings Deposited by Magnetron Sputtering

Abstract: Diamond-like carbon is one of the most studied and used solid lubricants on the market. Despite this large use and its outstanding mechanical and tribological properties, there are still some unclear aspects related to its self-lubricant properties, and some drawbacks in the deposition methods. We deposited “soft” DLC films on Si(100), iron, and stainless steel substrates by PVD magnetron sputtering technique with a Cr/CrN adhesive interlayer. The DLC films were characterized from a chemical, mechanical, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Carbon coatings are a very well investigated material used to improve multiple properties of the surface layer. They can be used to increase hardness [ 1 , 2 , 3 ], improve wear resistance, reduce the coefficient of friction [ 1 , 2 , 3 , 4 , 5 ] and enhance the biocompatibility of the modified surface [ 6 , 7 ] or its resistance to colonisation by micro-organisms [ 7 , 8 ]. Due to their advantages, diamond-like carbon (DLC) coatings are tested in a wide range of applications in very different areas: biomedicine [ 5 , 6 , 7 , 8 , 9 ], machining [ 10 , 11 ], electronics [ 12 , 13 ] and electrochemistry [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon coatings are a very well investigated material used to improve multiple properties of the surface layer. They can be used to increase hardness [ 1 , 2 , 3 ], improve wear resistance, reduce the coefficient of friction [ 1 , 2 , 3 , 4 , 5 ] and enhance the biocompatibility of the modified surface [ 6 , 7 ] or its resistance to colonisation by micro-organisms [ 7 , 8 ]. Due to their advantages, diamond-like carbon (DLC) coatings are tested in a wide range of applications in very different areas: biomedicine [ 5 , 6 , 7 , 8 , 9 ], machining [ 10 , 11 ], electronics [ 12 , 13 ] and electrochemistry [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, soft DLC films were deposited on Si (100), iron, and chrome steel substrates with a Cr adhesive interlayer using PVD magnetron sputtering technology [85]. The major output was to connect the coating chemical and mechanical behaviors to the various deposition parameters, such as discharge power and substrate-target distance.…”
Section: Tribological Properties Of Dlc Coatingsmentioning
confidence: 99%
“…The most popular process to synthesize a -C:H films is plasma-enhanced chemical vapor deposition (PECVD) [ 2 ]. The mechanical and tribological properties of a -C:H films depend on their atomic structure [ 3 ]. These films, and particularly what is called diamond-like carbon (DLC) films, have outstanding mechanical properties, such as high hardness, low coefficients of friction and excellent corrosion and wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…These films, and particularly what is called diamond-like carbon (DLC) films, have outstanding mechanical properties, such as high hardness, low coefficients of friction and excellent corrosion and wear resistance. Fiaschi et al reported that the hardness of DLC films depends on their sp 3 content and that the hardness affects tribological properties [ 3 ]. Many researchers have mentioned that the friction coefficient and specific rate of the films were affected by their hydrogen content [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%